A catalogue and taxonomic keys of the Subfamily Nicomachinae (Polychaeta: Maldanidae) of the world - de Assis, José Eriberto; Alonso, Carmen; Christoffersen, Martin Lindsey (Zootaxa, 2007)
A world catalogue and taxonomic keys of the subfamily Nicomachinae (Polychaeta: Maldanidae) are provided. Threegenera and 32 species are listed, complete with original references, synonyms, additional references, type localities, andtaxonomic remarks for those species which present some problem. Nicomache interstricta Ehlers, 1908 is transferred tothe genus Lumbriclymene Sars, 1872. Nicomache inornata Moore, 1903, Petaloproctus crosnieri Rullier, 1964, andPetaloproctus crenatus Chamberlin, 1919 are considered incertae sedis. Only three species of Nicomachinae have abroad geographical distribution.